Comparison of Serum Magnesium Levelin Diabetes Mellitus (DM) Patientswith or without Acute Coronary Syndrome (ACS) - Ratih Wulansari, -
Introduction: Until now, cardiovascular complications are still the highest cause of death and disability in DM patients. Hypomagnesemia in DM accelerate atherosclerosis and can cause instability and plaque rupture which can lead to acute coronary syndrome.